MANIFESTATION OF VIOLATIONS FINE MOTOR SKILLS IN CHILDREN WITH CEREBRAL PALSY (Conferencea, 2022)
Recently, very often talk about the importance and necessity of the development of fine motor skills in children. Fine motor skills are especially important in children with cerebral palsy.Many factors will depend on how fine motor skills of the hands are formed, such as the coordination of actions aimed at performing accurate small movements with the hands and fingers, which are necessary to dress, draw and write, as well as perform a large number of various household and educational activities; on the formation and development of the speech function of the child, in case of imperfection of these functions, the child may not socialize and adapt in society. Children with cerebral palsy have a number of features that characterize them; one of the features is a violation of the tone of the muscles of the hands, the presence of violent efforts, inaccuracy of hand movements and impaired limb formation [2]. Therefore, an important task for parents and teachers is the development of fine motor skills at an early and preschool age. What is fine motor skills and why is it so important in childhood and in particular for children with cerebral palsy?